Pattern of Presentation and Organ Involvement in Dengue Fever at Dhaka Medical College Hospital - Rahman, Motlabur; Hasan, Pratyay; Farheen, Tanjina; Islam, Md Khairul; Rashid, Md Harun Ur; Haque, Md Manjurul; Faruq, Imtiaz; Chowdhury, Jobayer Anam; Datta, Ponkaj Kanti (Journal of Dhaka Medical College, 2021)
Dengue fever first identified as ‘Dhaka Fever’ in 1964 & became endemic around 2000. The most recent spreading of dengue in 2019 was also notable for change in the presenting features of the patients attributed by some to the fact that causative virus might be of different serotype. Our study aims to assess the current pattern of presentation of dengue virus infection, done in inpatient of Department of Medicine of Dhaka Medical College Hospital Dhaka. This was a crosssectional, observational, descriptive study conducted between 1st August and 30th September 2019. A total 70 subjects, age >12 years were included in this study. Among them 55 were male & 15 were female, with a mean age of 28.33(±12.15) years. Comorbidities noticed in few cases such as DM (2, 2.90%), HTN (3, 4.35%), IHD (1,1.45%), CKD & COPD (1,1.45%). The most common presentation were fever (64, 91.43%), headache (62, 88.57%) anorexia (59, 85.51%), generalised pain (51, 73.91%), nausea (49, 71.01%). Examination findings at admission were temperature was high but not very high, pulse were normal, both systolic & diastolic pressure were somewhat normal, among the warning signs, severe abdominal pain (27.54%), persistent vomiting (21.74%), lethargy /restlessness /sudden behavioural change (21.74%) were most common. The common haematological parameters & routine investigation values were not deviated from expected range. As dengue is likely to continue to constitute a serious public health problem in Bangladesh, this study may help the practitioners to understand the changing pattern & to manage patients accordingly. J Dhaka Medical College, Vol. 28, No.2, October, 2019, Page 199-207